Let's talk about sex: Development and evaluation of a sexual history and counseling curriculum for internal medicine interns. Issue 7 (July 2018) - Shroff, Swati; Spataro, Brielle; Jeong, Kwonho; Rothenberger, Scott; Rubio, Doris; McNeil, Melissa
Highlights: Limited data on resident sexual history taking and STI counseling curricula exists. We developed a sexual history and counseling curriculum for medical interns. Interns reported higher proficiency obtaining a sexual history post-curriculum. Interns reported higher proficiency obtaining sexual histories from female versus male patients. Interns reported significantly higher rates of comfort with STI counseling post-curriculum. Abstract: Objective: We developed a curriculum to increase internal medicine interns' proficiency in sexual history taking and sexually transmitted illness (STI) counseling. Methods: The 4-h curriculum included didactics and interactive components, and was evaluated with matched pre- and post-surveys. Results: Twenty-one interns completed the curriculum. Mean knowledge score improved from 59% to 76% from pre- to post-curriculum ( P = 0.004 ). Median comfort score (Likert scale 1–5) with obtaining a sexual history improved from 3.8 [IQR 3.0, 4.0] to 3.8 [IQR 3.6, 4.6] and 3.8 [IQR 3.6, 4.0] to 4.1 [IQR 3.9, 4.8] for male ( P = 0.05 ) and female patients ( P = 0.007 ), respectively. Median frequency score for obtaining a sexual history improved from 2.9 [IQR 2.7, 3.0] to 3.1 [IQR 2.8, 3.4] and 3.2 [IQR 2.8, 3.7] to 3.4 [IQR 3.2, 4.0] for male ( P = 0.16 ) and female patients ( P = 0.008 ), respectively. Pre- and post- curriculum, interns reported significantly higher comfort and frequency in obtaining sexual histories from female vs. male patients. Post- curriculum, interns reported significantly higher comfort with positive STI counseling. Practice implications: Our curriculum improved interns' knowledge and comfort in sexual history taking and STI counseling. Future interventions should address sex disparities in sexual history taking.